White stallion of Lipizza - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Aladdin Books, 2014)
A baker's son, who dreams of becoming a riding master at Vienna's Spanish Court Riding School, is admitted as an apprentice and achieves his desire under the tutelage of both two-legged and four-legged masters.
Socials
Global
Ages 8-12.
Keywords: Spanische Reitschule (Vienna, Austria) -- Juvenile fiction; Spanish Riding School (Vienna, Austria) -- Fiction; Lipizzaner horse -- Juvenile fiction; Horsemanship -- Fiction; Lipizzaner horse -- Fiction; Horses -- Fiction